Implementation of Apriori Algorithm on Wet Cake Sales - Darmawan, Firmansyah Aji; Marisa, Fitri (Lumina Infinity Academy Foundation, 2026)
This research implements the Apriori algorithm on wet cake sales data to identify frequent purchase patterns. In an era of intense business competition, efficient inventory management and sales strategies are essential, especially for perishable products. Daily sales data is analyzed using a quantitative approach, focusing on support and confidence as the main parameters. The analysis results show product combinations that are often bought together, such as Bolu Pisang, Martabak, with a support value of 42.86% and confidence of 75.00%. The findings provide valuable insights for designing marketing and stock management strategies, which can improve business competitiveness and sustainability. This research also encourages the application of similar techniques in other business sectors to improve operational efficiency.